Finite-size effects of diffusion coefficients computed from molecular dynamics: a review of what we have learned so far. Issue 10 (24th July 2021) - Celebi, Alper T.; Jamali, Seyed Hossein; Bardow, André; Vlugt, Thijs J. H.; Moultos, Othonas A.
ABSTRACT: The number of molecules used in a typical Molecular Dynamics (MD) simulations is orders of magnitude lower than in the thermodynamic limit. It is therefore essential to correct diffusivities computed from Molecular Dynamics simulations for finite-size effects. We present a comprehensive review on finite-size effects of diffusion coefficients by considering self-, Maxwell–Stefan, and Fick diffusion coefficients in pure liquids, as well as binary, ternary, and quaternary mixtures. All finite-size corrections, both analytical and empirical, are discussed in detail. The finite-size effects of rotational and confined diffusion are also briefly discussed.